The Application of Perma Number 2 of 2012 Against Perpetrators of Minor Crimes In Deli Serdang Police Station - Bobby Tambunan; H. Abdul Razak Nasution; Mhd. Azhali Siregar (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
Supreme Court Regulation (Perma) Number 2 of 2012 concerning Adjustment of the Limitation of Minor Crimes and the Amount of Fines in the Criminal Code is a legal instrument that aims to simplify the process of handling minor crimes (tipiring) and reduce the burden on the judiciary. This Perma stipulates that cases with losses of less than IDR 2.5 million can be categorized as minor crimes, which allows for faster and more efficient resolution. This study aims to analyze the implementation of Perma Number 2 of 2012 against perpetrators of minor crimes at the Deli Serdang Police, including its effectiveness in investigative practices, obstacles faced by police officers, and its impact on the criminal justice system. The research approach used is empirical juridical, with data collection methods through interviews, observations, and analysis of cases handled by the Deli Serdang Police. The results of the study indicate that the implementation of Perma Number 2 of 2012 at the Deli Serdang Police provides benefits in accelerating the resolution of minor crimes, such as minor theft, minor assault, and other minor crimes. The implementation of this regulation allows cases to be resolved through a speedy trial mechanism, reducing the detention time for perpetrators, and optimizing the principle of simple, fast, and low-cost justice. However, there are a number of obstacles in implementation, including the lack of understanding of the community and law enforcement officers regarding the limits of the value of losses, the lack of synchronization between this regulation and the Criminal Code, and limited infrastructure in organizing speedy trials. The implementation of Perma Number 2 of 2012 at the Deli Serdang Police has had a positive impact on the efficiency of resolving minor crimes, but still requires optimization through wider socialization, increased coordination between law enforcers, and improvement of regulations to overcome obstacles in its implementation.